2022
DOI: 10.1007/s11606-021-07379-z
|View full text |Cite
|
Sign up to set email alerts
|

Health Status, Persistent Symptoms, and Effort Intolerance One Year After Acute COVID-19 Infection

Abstract: Background The long-term prevalence and risk factors for post-acute COVID-19 sequelae (PASC) are not well described and may have important implications for unvaccinated populations and policy makers. Objective To assess health status, persistent symptoms, and effort tolerance approximately 1 year after COVID-19 infection Design Retrospective observational cohort study using surveys and clinical data Participants Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 15 publications
2
41
1
8
Order By: Relevance
“…Hence, the viral regulation of host mitochondrial transcription occurs after the initial viral protein inhibition of mitochondrial protein function. Surprisingly, however, brain mitochondrial gene expression was affected possibly accounting for the commonly experienced “brain fog” ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the viral regulation of host mitochondrial transcription occurs after the initial viral protein inhibition of mitochondrial protein function. Surprisingly, however, brain mitochondrial gene expression was affected possibly accounting for the commonly experienced “brain fog” ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…While generally considered an inflammatory disease, recent evidence suggests that SARS-CoV-2 infection also inhibits mitochondrial bioenergetics, and that mitochondrial inhibition can activate of the inflammasome. Thus, in infected individuals, mitochondrial inhibition may not only contribute to excessive cytokine production but may be particularly impactful for the heart and brain, since these organs are highly reliant on mitochondrial energy production ( 15 ).…”
mentioning
confidence: 99%
“…Another study suggested that HIV was one factor associated with higher risk of PASC among those requiring emergency department or hospital-based care [32], but the analysis was limited to 10 PWH and did not include biological measurements. While our cohort is not representative of all individuals with SARS-CoV-2 infection and cannot estimate the population-level prevalence of PASC, the observation that persistent SARS-CoV-2-attributed symptoms were highly prevalent in PWH and that the adjusted odds of PASC were four-fold as high as in well-matched HIV-negative comparators was striking.…”
Section: Discussionmentioning
confidence: 99%
“…One single-center study suggested that acute illness severity in PWH was significantly associated with PASC with 44% of participants experiencing at least one symptom 30 days after recovery [40], however it did not find an association between clinical parameters such as CD4+ T cell count, viral load, demographics or comorbidities and the presence of PASC, and did not compare PWH with HIV-negative individuals. Another retrospective study suggested that HIV was one factor that was associated with higher risk of PASC approximately one year after COVID-19 diagnosis among those requiring emergency department or hospital-based care [56], but the analysis was limited to 10 PWH and did not include biological measurements. While our cohort is not representative of all individuals with SARS-CoV-2 infection and cannot be utilized to estimate the population-level prevalence of PASC in the overall population or among PWH, the observation that persistent SARS-CoV-2-attributed symptoms were highly prevalent in PWH and that the adjusted odds of PASC were nearly four-fold as high as in a relatively well-matched HIV-negative comparator group was striking.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirm persistence of symptoms in individuals with Long COVID up to 1 year [20][21][22] . We now add that 3 in 5 people with Long COVID have impairment in at least one organ, and 1 in 4 have impairment in two or more organs, in some cases without symptoms.…”
Section: Discussionmentioning
confidence: 84%